Optimization of City Water Supply Networks on Their Structural and Functional Analysis Base - Tkachuk, Alexander; Pilipaka, Lyudmila; Azizova, Anna (International Journal of Engineering and Technology, 2018)
Based on the research results on the operation of urban water supply and distribution systems, the most rational ways of their improvement are identified in order to improve water supply and energy saving. Â